AN ECONOMIC ANALYSIS OF THE FACTORS AFFECTING EGGS IMPORTING IN IRAQ FOR THE PERIOD (2003 – 2018 (AND PREDECTION THE EGGS IMPORTING FOR THE PERIOD (2019 – 2025) - Fawzi, A . T.; Alwasity, R. T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study aimed to determine the most important factors affecting importing of table eggs in Iraq for the period 2003 - 2018. To achieve the objectives the analysis phase was divided into two parts, the first was to measure factors affecting the importing of table eggs in order to obtain a mathematical relationship between the dependent variable (imports) and the independent variables represented by the local price of table eggs and the price limits for table eggs, the exchange rate, the national income, the population, the local production of table eggs, and  the number of table egg projects. The second stage was to predict for the period (2019-2025) using the simple regression method. The results showed that the continuous increase in the population will lead to an increase in the imported quantities of table eggs due to the increase in consumer demand for this product eggs, Most estimated parameters of importing function were significant at 5%. The highest expected amount of imported table eggs (10056 million eggs) on 2025, while the lowest  amount (7631.36 million eggs) on 2019. It can be concluded that there is no government policies in subsidizing production inputs and supporting the final product. The study recommended for a policy to protect domestic products from foreign competition.